2014
DOI: 10.1186/1471-2164-15-756
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiles of bovine in vivo pre-implantation development

Abstract: BackgroundDuring mammalian pre-implantation embryonic development dramatic and orchestrated changes occur in gene transcription. The identification of the complete changes has not been possible until the development of the Next Generation Sequencing Technology.ResultsHere we report comprehensive transcriptome dynamics of single matured bovine oocytes and pre-implantation embryos developed in vivo. Surprisingly, more than half of the estimated 22,000 bovine genes, 11,488 to 12,729 involved in more than 100 path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
171
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(203 citation statements)
references
References 57 publications
30
171
2
Order By: Relevance
“…In agreement with a previous study (Jiang et al, ), we found that approximately half of all annotated protein‐coding genes are expressed in bovine oocytes. More of these genes were detected in GV‐ than in MII‐stage oocytes, with a large proportion of these genes decreasing in abundance compared to those that increased as maturation proceeded; similar trends were observed in other studies utilizing oocytes from bovine (Fair et al, ; Mamo et al, ), human (Assou et al, ), and Xenopus tropicalus (Graindorge et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a previous study (Jiang et al, ), we found that approximately half of all annotated protein‐coding genes are expressed in bovine oocytes. More of these genes were detected in GV‐ than in MII‐stage oocytes, with a large proportion of these genes decreasing in abundance compared to those that increased as maturation proceeded; similar trends were observed in other studies utilizing oocytes from bovine (Fair et al, ; Mamo et al, ), human (Assou et al, ), and Xenopus tropicalus (Graindorge et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of mapped reads ranged from 90.22% to 92.81%, and the rate of clean Q30 bases ranged from 94.70% to 95.94% (Table S1). The total numbers of detectable genes ranged from 11,772 to 12,655 in the control and vitrification groups (Table , Table S2), and were similar to those reported previously for bovine oocytes (Jiang et al., ).…”
Section: Resultssupporting
confidence: 86%
“…A total of 9,827–14,893 transcripts were detected in each in vitro stage (Table ). In general, this result was very similar to the findings in in vivo bovine embryos, but a much lower number of transcripts were detected at the blastocyst stage compared with the transcriptomes of bovine embryos (Graf et al., ; Jiang et al., ; Kues et al., ). This might reflect the suboptimal conditions of current IVC system for yak embryos.…”
Section: Discussionsupporting
confidence: 85%
“…The development of RNA sequencing technologies permits the study of gene regulation at an unprecedented level. Most studies have been conducted in the mouse, human and bovine (Cao et al., ; Graf et al., ; Jiang et al., ; Xie et al., ); however, regulation of yak embryonic gene expression still remains poorly understood. The application of RNA‐Seq in embryos is limited by the low RNA content of a single pre‐hatching bovine embryo (200–2,300 pg) depending on the stage of the development (Gilbert et al., ).…”
Section: Discussionmentioning
confidence: 99%